SOSIALISASI PENGIRIMAN BARANG INTERNASIONAL DENGAN TRANSPORTASI MULTIMODAL KEPADA PERUSAHAAN JASA PENGIRIMAN DI KOTA DENPASAR - Salain, M.S.P.D.; Santosa, A.A.G.D.H.; Yasa, M.M.; Satyawati, N.G.A.D. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i01.p11, 2023)
The increase in international trade is followed by the increasing use of international freight forwarding services. Problems appear frequently when the goods sent are lost, swapped, or damaged especially in multimodal transportation. At what stage the goods sent are lost or damaged and who is the responsible party for it? The problem is getting more complicated when the goods was sent by a third party. The third parties as sub-contracted couriers may limit their liability in the freight forwarding contract by using the “Himalaya Clause” according to the lost/damaged goods. In practice, several freight forwarding/cargo companies that use multimodal transportation in Denpasar have a problem in drafting the shipping documents and liability of the parties when the goods are lost/swapped/damaged. Therefore, the Community Service Team socializing the international shipping procedure with multimodal transportation to the freight forwarder/cargo companies in Denpasar. This socialization aims to prevent a dispute between the parties involved thus it will give legal certainty to the freight forwarder/cargo companies and their consumers. Keywords: Denpasar; Freight Forwarder Company; International; Multimodal Transportation; Socialization.